Golden giggles at Rumah Ehsan Kuala Kubu Bharu: ketawa bersama, sihat sentiasa - Zuleffend, Ibrahim; Ismail, Nurul Safiyah; Mat Ruzlin, Aimi Nadira; Roslan, Dalila; Ahmad Saman, Mohd Shahril; Xin Wee, Chen (Faculty of Medicine, 2025)
On 5 May 2025, in conjunction with World Laughter Day, postgraduate students from the Master of Public Health (MPH) program at UiTM Sungai Buloh brought joy to an Old Folks Home in Kuala Kubu Bharu. The group, comprising 17 students and four lecturers, was warmly greeted by the administrators and residents of Rumah Ehsan, Kuala Kubu Bharu. The mini health promotion program, called Golden Giggles, was held as part of the Society, Behaviour & Health, and Population Health & Dynamics courses.